INOVASI MANAJERIAL KEPALA SMK BERBASIS PESANTREN (Studi Multi Kasus SMK Pesantren di Banyuwangi) - Kholilur Rahman (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2015)
This preliminary study aims to identify, describe and analyze innovation-based head of vocational schools as well as their implications, particularly with regard to managerial innovation. Reality later showed the proliferation of schools in Banyuwangi establish formal educational institutions, particularly vocational schools (SMK). Though conceptually management, between schools and vocational embracing the concept of different management. Management schools tend to be centralized, while the vocational school as a formal educational institution adheres desentralitik management system. Thus, it does require changes in the system, both organizationally and managerially. One side of the Head of SMK should be able to secure the values uniquely pesantren as the "owner" SMK. On the other hand, the Head of SMK demanded to carry out government policy as a regulator. If between the school and the government have the same concept, the heads SMK implement its stay in the school's policy, but if the government mandates between schools and different policies, then this is where the head of CMS is required to find the concept of managerial innovation for the continuation of its stakeholders